Evolutionary and Structural Features of the C2, V3 and C3 Envelope Regions Underlying the Differences in HIV-1 and HIV-2 Biology and Infection - Barroso, Helena (Public Library of Science, 2011)
BACKGROUND: Unlike in HIV-1 infection, the majority of HIV-2 patients produce broadly reactive neutralizing antibodies, control viral replication and survive as elite controllers. The identification of the molecular, structural and evolutionary footprints underlying these very distinct immunological and clinical outcomes may lead to the development of new strategies for the prevention and treatment of HIV infection. METHODOLOGY/PRINCIPAL FINDINGS: We performed a side-by-side molecular, evolutionary and structural comparison of the C2, V3 and C3 envelope regions from HIV-1 and HIV-2. These regions contain major antigenic targets and are important for receptor binding. In HIV-2, these regions also have immune modulatory properties. We found that these regions are significantly more variable in HIV-1 than in HIV-2. Within each virus, C3 is the most entropic region followed by either C2 (HIV-2) or V3 (HIV-1). The C3 region is well exposed in the HIV-2 envelope and is under strong diversifying selection suggesting that, like in HIV-1, it may harbour neutralizing epitopes. Notably, however, extreme diversification of C2 and C3 seems to be deleterious for HIV-2 and prevent its transmission. Computer modelling simulations showed that in HIV-2 the V3 loop is much less exposed than C2 and C3 and has a retractile conformation due to a physical interaction with both C2 and C3. The concealed and conserved nature of V3 in the HIV-2 is consistent with its lack of immunodominancy in vivo and with its role in preventing immune activation. In contrast, HIV-1 had an extended and accessible V3 loop that is consistent with its immunodominant and neutralizing nature. CONCLUSIONS/SIGNIFICANCE: We identify significant structural and functional constrains to the diversification and evolution of C2, V3 and C3 in the HIV-2 envelope but not in HIV-1. These studies highlight fundamental differences in the biology and infection of HIV-1 and HIV-2 and in their mode of interaction with the human immune system and may inform new vaccine and therapeutic interventions against these viruses.